2009
DOI: 10.1038/cdd.2009.164
|View full text |Cite
|
Sign up to set email alerts
|

NF45 functions as an IRES trans-acting factor that is required for translation of cIAP1 during the unfolded protein response

Abstract: Expression of the cellular inhibitor of apoptosis protein 1 (cIAP1) is unexpectedly repressed at the level of translation under normal physiological conditions in many cell lines. We have previously shown that the 5′ untranslated region of cIAP1 mRNA contains a stress-inducible internal ribosome entry site (IRES) that governs expression of cIAP1 protein. Although inactive in unstressed cells, the IRES supports cap-independent translation of cIAP1 in response to endoplasmic reticulum stress. To gain an insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 44 publications
1
72
1
Order By: Relevance
“…The MALDI-TOF mass spectrometry analysis of cIAP1 IRES captured proteins identified them as RNA Helicase A (RHA), insulin-like growth factor 2 mRNA binding protein 1 (IGF2BP1), NF90 and NF45 ( Figure 5C). Furthermore, Western blot analysis using antibodies against RHA, IGF2BP1, NF90 and NF45 confirmed that these proteins specifically interact with the cIAP1 IRES but not with the non-IRES portion of the cIAP1 5' UTR ( Figure 5D) (Graber et al, 2010). …”
Section: Avidin-biotin Rna-affinity Chromatography Isolation Of Xiap mentioning
confidence: 85%
See 4 more Smart Citations
“…The MALDI-TOF mass spectrometry analysis of cIAP1 IRES captured proteins identified them as RNA Helicase A (RHA), insulin-like growth factor 2 mRNA binding protein 1 (IGF2BP1), NF90 and NF45 ( Figure 5C). Furthermore, Western blot analysis using antibodies against RHA, IGF2BP1, NF90 and NF45 confirmed that these proteins specifically interact with the cIAP1 IRES but not with the non-IRES portion of the cIAP1 5' UTR ( Figure 5D) (Graber et al, 2010). …”
Section: Avidin-biotin Rna-affinity Chromatography Isolation Of Xiap mentioning
confidence: 85%
“…Exactly how ITAFs modulate IRES activity is not clear; ITAFs were suggested to act as adapter proteins which act as a bridge between the ribosome and mRNA (Mitchell et al, 2005), or as RNA chaperones which remodel mRNA into a conformation that permits ribosome recruitment (Yaman et al, 2003). We have been studying IRES-mediated translation of cellular mRNAs during stress using two anti-apoptotic proteins, X chromosome-linked inhibitor of apoptosis (XIAP) and cellular inhibitor of apoptosis protein 1 (cIAP1), as model systems (Holcik et al, 1999;Graber et al, 2010;Riley et al, 2010;Thakor & Holcik, 2011). To gain full understanding of the regulation and function of XIAP and cIAP1 IRESes, it was necessary to isolate and identify ITAFs which modulate IRES activity.…”
Section: Fig 1 Schematic Diagram Of Cap Dependent Translation Initimentioning
confidence: 99%
See 3 more Smart Citations